2019
DOI: 10.1016/j.jmb.2019.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of the TGF-β Signaling Pathway

Abstract: Transforming growth factor beta (TGF-β) is an important growth factor that plays essential roles in regulating tissue development and homeostasis. Dysfunction of TGF-β signaling is a hallmark of many human diseases. Therefore, targeting TGF-β signaling presents broad therapeutic potential. Since the discovery of the TGF-β ligand, a collection of engineered signaling proteins have been developed to probe and manipulate TGF-β signaling responses. In this review, we highlight recent progress in the engineering of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 107 publications
0
25
0
2
Order By: Relevance
“…Similarly, we found the m6A-related AS events in the TGF-β signaling in LUSC. The TGF-β signaling pathway was frequently downregulated in human cancers (Syed, 2016), whereas this pathway activation could also promote tumorigenesis, metastasis, and chemoresistance (Colak and Ten Dijke, 2017;Zi, 2019). In this regard, genes of the m6A-related AS event-led activation of the TGF-β signaling could promote LUSC tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we found the m6A-related AS events in the TGF-β signaling in LUSC. The TGF-β signaling pathway was frequently downregulated in human cancers (Syed, 2016), whereas this pathway activation could also promote tumorigenesis, metastasis, and chemoresistance (Colak and Ten Dijke, 2017;Zi, 2019). In this regard, genes of the m6A-related AS event-led activation of the TGF-β signaling could promote LUSC tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We further analyzed the high-risk and low-risk groups by GSEA, and it can be found that the following pathways are enriched: TGF-beta signaling, Angiogenesis, Wnt/β-catenin-mediated signaling, epithelialmesenchymal transition, Hypoxia, KRAS signaling up, Hedgehog signaling Coagulation, Myogenesis, Apical surface, Apical-junction, NV-response-DN, Apoptosis. According to research, TGF-beta signaling is an important regulatory growth factor in our body, which mainly maintains the development of tissues and the homeostasis of the internal environment, so it is related to the onset of many diseases 34 . Previous reports have shown that RBPs participate in these pathways and affect tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…19,23,24 Pensinyalan TGF-β Superfamili Transforming Growth Factor (TGF-β) merupakan kelompok besar sitokin dengan 32 anggota, termasuk TGF-βs, aktivin, inhibin, nodal, Growth and Differentiation Factors (GDF), dan Bone Morphogenetic Proteins (BMP). 32,33 Masing-masing memiliki peran penting dalam banyak proses seluler, khususnya dalam perkembangan embrionik dan homeostatis jaringan dewasa, 34 homeostatis dan toleransi imun 35 serta terlibat dalam tumorigenesis dengan fungsi ganda TGF-β sebagai supresor dan promotor tumor. [36][37][38] Selama fase awal pembentukan tumor, TGF-β menunjukkan peran supresor yang kuat dengan menghambat perkembangan siklus sel dan menginduksi apoptosis, 39 sedangkan pada fase perkembangannya, sel-sel tumor secara bertahap menjadi resisten terhadap efek antimitogeniknya dan TGF-β dapat beralih menjadi promotor tumor, memfasilitasi Epithelial-Mesenchymal Transition (EMT), angiogenesis tumor, invasi dan metastasis.…”
Section: Gambar 3 Pensinyalan Non-kanonikal Wntunclassified
“…36,39 Jalur non-kanonikal TGF-β TGF-β mengarahkan beberapa efek biologis dalam jalur non-kanonikalnya dengan cara menginduksi beberapa jalur pensinyalan melalui aktivasi SMAD jalur TGF-β independen. 32 Aktivasi pensinyalan TGF-β non-kanonik dimulai dengan pengikatan TGF-β terhadap reseptornya yang menstimulasi berbagai kinase, termasuk phosphatidylinositol 3-kinase (PI3K)/protein kinase B (PKB/ AKT), mitogen-activated protein kinase (MAPK), nuclear factor κβ (NF-κβ), Ras homolog (Rho), TGF-β1 activated kinase 1 (TAK1), tumor necrosis factor receptorassociated factor 4 dan 6 (TRAF4, TRAF6), yang di antaranya terdapat fokus utama pada tiga pertama sinyal yang dilaporkan memiliki relevansi tertinggi dengan TGF-β dalam perkembangan kanker. 35,52 SMAD terdiri dari dua domain dan sebuah daerah penghubung (linker region), dan kinase tersebut mampu untuk memfosforilasi daerah penghubung SMAD2/3, yang merupakan wilayah antara domain N-terminus Mad-homology 1 (MH1) dan C-terminus MH2 dari protein SMAD.…”
Section: Gambar 4 Pensinyalan Tgf-βunclassified